Investigation of the Human MG63 Osteoblastic Cell Response to Nanotubular Surfaces - Berthelot, Ryan (Université d'Ottawa | University of Ottawa, 2024)
Cells found within bone tissues, and in particular osteoblasts, are profoundly influenced by the nanotopographical features of their extracellular environment which play a critical role in orchestrating osteogenesis, cellular differentiation, and bone mineralization, via a wide range of mechanical and biochemical signals. Advances in materials science and nanotechnology have made possible to create substrates and interfaces with intricate nano-patterns that interact with cells at the molecular level, offering unprecedented opportunities to investigate the mechanisms that control cellular interactions with both natural and synthetic surfaces. The development of micro-and nano-engineered surfaces has been one of the main factors that has spurred the advances in bone tissue engineering. However, the development of more effective surfaces capable of predictively dictate a beneficial cellular response also requires a deep understanding of how to account for the complex and variable conditions of the native bone microenvironment. In this Thesis, nanotopographical and environmental variables were incorporated by investigating the role of cellular preconditioning in elevated glucose levels and the ability of optimized, single diameter titanium nanotubular surfaces to modify the preconditioned behavior via direct physicochemical cueing. In further pursuit of optimal parameters, the integration of high-throughput screening processes for evaluating these surfaces has aroused interest for the rapid identification of nanotopographical features that best support osteogenesis. Multivariable testing via nanotopographical gradients can help address this need, accelerating the development of effective surfaces and enhance our ability to rapidly tailor surface properties to specific real-world applications. As the field advances, the design and implementation of nanotopographical surfaces that can effectively direct osteoblast behavior will be pivotal in creating next-generation biomaterials. The future of bone tissue engineering lies in the ability to create specialized surface designs with a nuanced understanding of cellular dynamics to achieve superior outcomes in bone health and regeneration. The overarching goal of my doctoral work was to engineer nanotopographical surfaces with tailored structural complexities to elicit specific osteoblastic responses. This approach aims to optimize surface properties for enhanced bone tissue engineering applications, including promoting osteogenic differentiation, reducing experimental variability from both environmental and surface features, and creating high-throughput platforms for rapid biomaterial screening. In the first study (Chapter 2), I investigated the combined influence of nanotopographical cues and environmental factors on human MG63 osteoblastic cell behavior. Using a triphasic anodization protocol, I created highly ordered single nanotube surfaces with varying tube diameters and compared these with a complex honeycomb architecture. I also modulated the glucose content in the culture medium to simulate normal and hyperglycemic conditions, incorporating a preconditioning step to ensure cells adapted to the altered environment. I then systematically analyzed cellular responses, including proliferation, migration, viability, and differentiation, under these different conditions to uncover potential synergistic or antagonistic effects between the nanotopographical features and environmental factors. In the second study (Chapter 3), I explored the influence of hierarchical nanotubular gradients on cell response, focusing on the complexity of the two-tiered, honeycomb architecture. I used a bipolar anodization process to create these surfaces, which featured a gradient of increasing disorder end-to-end, transitioning from single tubes into complex honeycomb topography. The study assessed the impact of these nanotopographical variations on cellular responses, including proliferation, differentiation, and migration. My findings highlighted the significant role of nanotopographical complexity, particularly in promoting osteogenic differentiation. I developed a high throughput testing process, aimed at shortening the time required to troubleshoot and optimize cell response, culminating in the extraction and synthesis of the most and least favorable surfaces, for further testing and validation of this process. In the third study (Chapter 4), I investigated MG63 osteoblastic cell behavior on rationally selected titanium nanotubular surfaces that were extracted from the previously developed gradient anodization process. These surfaces validated the high-throughput approach by confirming cell responses across the two topographies and provided deeper insights into the interactions between cells and surfaces of different complexities. Lastly, I established a Raman confocal imaging protocol on opaque, light-sensitive titanium, identifying key biochemical features of single cells and bone-like mineral for future research, demonstrating the feasibility of this technique for further study.
Keywords: Titanium Nanotubes; MG63; biocompatibility; Osteoblast; Glucose Preconditioning; Biomaterial Implants; Nanotopography; Hyperglycemia